2021
DOI: 10.1186/s12970-021-00415-7
|View full text |Cite
|
Sign up to set email alerts
|

Tomato powder is more effective than lycopene to alleviate exercise-induced lipid peroxidation in well-trained male athletes: randomized, double-blinded cross-over study

Abstract: Background Consumption of nutritional supplements to optimize recovery is gaining popularity among athletes. Tomatoes contain micronutrients and various bioactive components with antioxidant properties. Many of the health benefits of tomatoes have been attributed to lycopene encouraging athletes to consume pure lycopene supplements. The aim of this study was to compare the effect of tomato powder and lycopene supplement on lipid peroxidation induced by exhaustive exercise in well-trained male a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…This study confirmed the abundance of bioactive substances in oats, and the Daeyang cultivar had higher amounts of fat-soluble antioxidants than the Choyang oats. We believe these fat-soluble as well as water-soluble bioactive substances in oat synergistically interact, as previously reported in other plant bioactives in vitro [30][31][32] and in vivo [33], to exert antioxidant functions in the biological system.…”
Section: Bioactive Components Of Oat (Avena Sativa) Extractssupporting
confidence: 78%
“…This study confirmed the abundance of bioactive substances in oats, and the Daeyang cultivar had higher amounts of fat-soluble antioxidants than the Choyang oats. We believe these fat-soluble as well as water-soluble bioactive substances in oat synergistically interact, as previously reported in other plant bioactives in vitro [30][31][32] and in vivo [33], to exert antioxidant functions in the biological system.…”
Section: Bioactive Components Of Oat (Avena Sativa) Extractssupporting
confidence: 78%
“…Several studies have shown that isolated bioactive compounds (e.g., vitamin C, vitamin E, and lipoic acid) may have adverse effects on signs and adaptive responses to exercise (19,20) . In contrast, no evidence of such relations following the consumption of antioxidant-rich foods and/or extracts was reported (21,22) . https://doi.org/10.1017/S0007114522002124 Published online by Cambridge University Press…”
Section: Introductionmentioning
confidence: 97%
“…Beta-carotene is a dietary proteinoid enzymatically converted in the gut to retinoid. Carotenoids might help protect immune cells from oxidative damage, thus enhancing their immune function [ 39 , 40 ]. Selenium, a trace mineral found in grains, vegetables, seafood, meat, dairy products, and nuts [ 41 ], is linked to immune response through its incorporation into selenoproteins.…”
Section: Introductionmentioning
confidence: 99%